Construction of a High-Density Linkage Map and QTL Fine Mapping for Growth- and Sex-Related Traits in Channel Catfish (Ictalurus punctatus) - Zhang, Shiyong; Zhang, Xinhui; Chen, Xiaohui; Xu, Tengfei; Wang, Minghua; Qin, Qin; Zhong, Liqiang; Jiang, Hucheng; Zhu, Xiaohua; Liu, Hongyan; Shao, Junjie; Zhu, Zhifei; et al. (Frontiers in Genetics, 2019)
A high-density genetic linkage map is of particular importance in the fine mapping for important economic traits and whole genome assembly in aquaculture species. The channel catfish (Ictalurus punctatus), a species native to North America, is one of the most important commercial freshwater fish in the world. outside of the United States, China has become the major producer and consumer of channel catfish after experiencing rapid development in the past three decades. In this study, based on restriction site associated DNA sequencing (RAD-seq), a high-density genetic linkage map of channel catfish was constructed by using single nucleotide polymorphisms (SNPs) in a F1 family composed of 156 offspring and their 2 parental individuals. A total of 4,768 SNPs were assigned to 29 linkage groups (LGs), and the length of the linkage map reached 2480.25 cM with an average distance of 0.55 cM between loci. Based on this genetic linkage map, 223 genomic scaffolds were anchored to the 29 LGs of channel catfish, and a total length of 704.66 Mb was assembled. Quantitative trait locus (QTL) mapping and genome-wide association analysis identified 10 QTLs of sex-related and 6 QTLs of growth-related traits at LG17 and LG28, respectively. Candidate genes associated with sex dimorphism, including spata2, spata5, sf3, zbtb38 and fox, were identified within QTL intervals on the LG17. A sex-linked marker with simple sequence repeats (SSR) in zbtb38 gene of the LG17 was validated for practical verification of sex in the channel catfish. Thus, the LG17 was considered as a sex-related linkage group. Potential growth-related genes were also identified, including important regulators such as megf9, npffr1 and gas1. In a word, we constructed the high-density genetic linkage map and developed the sex-linked marker in channel catfish, which are important genetic resources for future marker-assisted selection (MAS) of this economically important teleost.